Artificial intelligence in education: Next-gen teacher perspectives - Nicoleta Sămărescu; Robert Bumbac; Alin Zamfiroiu; Maria-Cristina Iorgulescu (Amfiteatru Economic, 2024)
The progress made by artificial intelligence (AI) worldwide has led, through the Beijing Consensus, UNESCO to recommend to governments, in 2019, to include AI in educational policies and processes. While numerous studies inventory students' and teachers' opinions on the use of AI in education (AIEd), this article differs by analysing the factors that influence the behavioural intention to use AI from the training stage of future primary and secondary teachers in Romania. Through exploratory quantitative research, carried out on a sample of 270 students from the Faculty of Education, Social Sciences and Psychology, the interaction of subjects with AI and the intention of integrating AIEd are followed using binary logistic regression. The analysis conducted shows that among the six variables of the model, "the confidence in personal ability to use AI" and "the perception of a greater number of advantages" have a positive and significant impact on the willingness to use AI in the educational process, more than "being previously used", "the knowledge level" or "student requirements". These findings are of particular importance for the revision of teacher training programmes and the development of educational policies that increase the confidence of future teachers in the ability to use AI, eliminating fears or misconceptions about AI.
Keywords: O33; I20; 330; artificial intelligence; education; technology; future teachers; teacher training; behaviour intention; Technology Acceptance Model (TAM)